A multi‐omic study reveals BTG2 as a reliable prognostic marker for early‐stage non‐small cell lung cancer. Issue 6 (4th May 2018) - Shen, Sipeng; Zhang, Ruyang; Guo, Yichen; Loehrer, Elizabeth; Wei, Yongyue; Zhu, Ying; Yuan, Qianyu; Moran, Sebastian; Fleischer, Thomas; Bjaanæs, Maria M.; Karlsson, Anna; Planck, Maria; et al.
Abstract : B‐cell translocation gene 2 ( BTG2 ) is a tumour suppressor protein known to be downregulated in several types of cancer. In this study, we investigated a potential role for BTG2 in early‐stage non‐small cell lung cancer (NSCLC) survival. We analysed BTG2 methylation data from 1230 early‐stage NSCLC patients from five international cohorts, as well as gene expression data from 3038 lung cancer cases from multiple cohorts. Three CpG probes (cg01798157, cg06373167, cg23371584) that detected BTG2 hypermethylation in tumour tissues were associated with lower overall survival. The prognostic model based on methylation could distinguish patient survival in the four cohorts [hazard ratio (HR) range, 1.51–2.21] and the independent validation set (HR = 1.85). In the expression analysis, BTG2 expression was positively correlated with survival in each cohort (HR range, 0.28–0.68), which we confirmed with meta‐analysis (HR = 0.61, 95% CI 0.54–0.68). The three CpG probes were all negatively correlated with BTG2 expression. Importantly, an integrative model of BTG2 methylation, expression and clinical information showed better predictive ability in the training set and validation set. In conclusion, the methylation and integrated prognostic signatures based on BTG2 are stable and reliable biomarkers for early‐stage NSCLC. They may have new applications for appropriate clinical adjuvant trials and personalized treatments in the future. Abstract : In this multicenter study including 1230 tumor samples with methylation data and 3038 cases with gene expression data, we investigated the prognostic role of BTG2 and proposed a prognostic signature based on three CpG probes within BTG2 region and an integrated signature, which significantly stratified patients into low‐ and high‐risk groups and were more pronounced in the cases with adjuvant therapy. These markers may be relevant for developing novel therapies in the future.